Performance and Welfare of Sows Exposed to Auditory Environmental Enrichment in Mixed or Collective Housing Systems - Palermo Mendes, Janaina; Ribeiro Caldara, Fabiana; de Castro Burbarelli, Maria Fernanda; Valentim, Jean Kaique; Ferreira de Brito Mandú, Daniela; Garófallo Garcia, Rodrigo; Correia de Lima Almeida-Paz, Ibiara [UNESP]; Markiy Odakura, Agnes; Lourenço da Silva, Marconi Italo [UNESP] (MDPI, 2023)
The research aimed to assess the effects of auditory environmental enrichment on sows in mixed housing (caged until 35 days after insemination and then collective pens) or collective housing (caged until 72 h after insemination and then collective pens). Reproductive performance, body surface and eye temperature (ET) were evaluated as sows’ welfare indicators. A sample of 56 sows between 2nd and 6th parity was submitted to the treatments from artificial insemination to weaning. The sows were assigned in a randomized block design with a 2 × 2 factorial scheme of treatments: mixed housing—control (MH-C), collective housing—control (CH-C), mixed housing—music (MH-M) and collective housing—music (CH-M). Auditory enrichment consisted of exposing sows daily throughout gestation and lactation to 6 h of classical music divided into 2 h periods. The ET of pregnant sows in collective housing was lower than that of sows in mixed housing (33.77 °C vs. 34.91 °C). Pregnant and lactating sows exposed to auditory environmental enrichment exhibited lower ET compared to those that had no access to the stimulus (pregnant 33.36 °C vs. 34.32 °C and lactating 34.21 °C vs. 34.83 °C). No housing type effect was found on the reproductive performance parameter; however, piglets from sows submitted to auditory environmental enrichment, regardless of the type of housing during gestation, were heavier at weaning (6.32 kg vs. 5.57 kg). Collective or mixed housing does not affect sows’ reproductive performance; perhaps, auditory environmental enrichment reduced stress in the gestation and lactation phases and provided greater piglet weight gain at weaning.
Keywords: animal welfare; auditory stimulus; environmental enrichment; infrared thermography; reproductive performance; swine